Detection of Genetic Replica Robots Using Wireless Sensor Networks. - Sathya, V.; S.Kannan, Dr. (International Journal of Engineering and Technology, 2018)
The collaboration between wireless sensor networks and the distributed robotics has prompted the making of mobile sensor networks. It is also a  key enabler for a range of advanced hybrid applications, such as environmental monitoring and Ambient Assisted Living (AAL).  We also refer this work to be a robotic wireless sensor networks.  The reduction in costs of mobile sensor networks and their expanding capacities makes mobile sensor networks conceivable and useful. Today, many types of research are focused on the making of mobile wireless sensor networks due to their favorable advantage and applications. By using this strategy we focus on detecting the genetic (clone) robots in a cluster of robots which passes the intercepted and fabricated messages to the other robots.  A novel algorithm called Snow Ball Endurance Algorithm (SBEA) has been proposed here to detect the cloned robots in a cluster of robots.  Also, this paper focuses on Mobile Wireless Sensor Networks (MWSN) and robotics which plays a crucial role if it integrated with static nodes to become a Mobile Robot, which can enhance the capabilities, and enables their new applications.  Finally the algorithm has been implemented with a cluster of robots and the simulated results have been given out.